interior of the city - Grigoryeva, Elena (project baikal, 2018)
The spring started with two popular architectural events in Siberia: in the beginning of March the youth Archbukhta was held in Irkutsk (8), and at the end of the same month the Archigesh was organized for mountain skiers in Novokuznetsk (12). After determination of the winners, our attention was focused on the city environment, the most trending topic of the season. Spring is the best season to take care of the city environment in general and of urban improvement in particular, because the snow melts to uncover all drawbacks of the surface relief. At the same time, contractors wake up from hibernation and are ready to manage the allocated funds. Citizens choose (now by themselves!) the public spaces to be financed by those funds. And so, the interior of the city. In April small towns and historic settlements of our big country prepared submissions to the city environment competition opened by the Ministry of Construction. At the end of May, already under the new Minister of Construction, the results of the competition were announced (40). The winners were congratulated by the Prime-Minister. The rest of the participants cannot but hope that this useful competition will be held annually. The criteria included identity: its recognizing, preservation and even creation. Already in June, Irkutsk architects, urbanists, historians and sociologists discussed the same (their favourite) topic at the Project Baikal Discussion Club Meeting held at a new place, “Boiling Point” (88). The object of the issue is Zaryadye in Moscow, a brand-new urban interior of the capital (131).